Catalysis : an integrated approach - Santen, R. A. van (Rutger A.); ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1999)
This book concentrates on industrially relevant reactions which are catalyzed by heterogeneous and homogeneous catalysts. Homogeneous catalysis by metal complexes is treated jointly with heterogeneous catalysis using metallic and non-metallic solids. In both areas the high degree of sophistication of spectroscopic techniques and theoretical modelling has led to an enormous increase in our understanding at the molecular level. This holds for the kinetics of the reactions and the reactivities of the catalysts, as well as for the syntheses of the catalytic materials. The development of catalysis science since the first edition of this book has necessitated a thorough revision, including special chapters on biocatalysis, catalyst characterization and adsorption methods. The multidisciplinary nature of catalysis is reflected in the choice of a novel combination of basic disciplines which will be refreshing and inspiring to readers.
History of catalysis / A.P. Kieboom [and others] -- Catalytic processes in industry / A.P.G. Kieboom [and others] -- Chemical kinetics of catalyzed reactions / F. Kapteijn [and others] -- Bonding and elementary steps in catalysis / B.A. Averill [and others] -- Heterogeneous catalysis / B.K. Hodnett [and others] -- Homogeneous catalysis with transition metal complexes / G. van Koten and P.W.N.M. van Leeuwen -- Biocatalysis / B.A. Averill [and others] -- Catalytic reaction engineering / F. Kapteijn, G.B. Marin and J.A. Moulijn -- Preparation of catalyst supports, zeolites and mesoporous materials / E.B.M. Doesburg, K.P. de Jong and J.H.C. van Hooff -- Preparation of supported catalysts / J.W. Geus and J.A.R. van Veen -- Catalyst characterization with spectroscopic techniques / J.W. Niemantsverdriet -- Catalyst characterization and mimicking pretreatment procedures by temperature-programmed techniques / F. Kapteijn, J.A. Moulijn and A. Tarfaoui -- Adsorption methods for the assessment of the specific surface area and the pore size distribution of heterogeneous catalysts / J.A. Lercher.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Catalysis; SCIENCE -- Chemistry -- Physical & Theoretical; Catalysis; Electronic books